2015
DOI: 10.1074/jbc.m115.672659
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in the Myocyte Enhancer Factor 2 (MEF2)-regulated Gtl2-Dio3 Noncoding RNA Locus Promote Cardiomyocyte Proliferation by Targeting the Transcriptional Coactivator Cited2

Abstract: Background: MicroRNAs have recently emerged as key regulatory molecules in cardiomyocyte proliferation. Results: miR-410 and miR-495 are regulated by MEF2 in cardiomyocytes, and their overexpression results in increased cardiomyocyte proliferation. Conclusion: miR-410 and miR-495 potently induce cardiomyocyte proliferation by directly inhibiting the coactivator Cited2. Significance: These findings reveal novel microRNAs that can be modulated to stimulate the regeneration of damaged cardiac tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 56 publications
(53 reference statements)
2
52
0
Order By: Relevance
“…For example, the expression of muscle-related genes is regulated coordinately by well-known transcriptional factors including serum response factor (SRF), myocyte enhancer factor 2 (MEF2) and other transcription factors (13).…”
Section: Biology Of Mir-499 In Cardiomyocyte Developmentmentioning
confidence: 99%
“…For example, the expression of muscle-related genes is regulated coordinately by well-known transcriptional factors including serum response factor (SRF), myocyte enhancer factor 2 (MEF2) and other transcription factors (13).…”
Section: Biology Of Mir-499 In Cardiomyocyte Developmentmentioning
confidence: 99%
“…However, the role of miRNAs in the adaptation of the RV to pressure and volume overload and the transition to RV failure remains unclear. We focused on miR-495 in right heart hypertrophy for the following reasons: (1) miR-495 was initially identified as one of the deregulated miRNAs in the Gtl2-Dio3 locus; (2) miR-495 is upregulated in multiple models of cardiac disease and is associated with prohypertrophy; its inhibition in stressed cardiomyocytes thus attenuates the pathological growth response [17]; and (3) the Gtl2-Dio3 locus is also regulated by myocyte enhancer factor 2 (MEF2) in cardiac muscle [15,17]. MEF2 has been implicated in RV development, regulating the metabolic, contractile, and angiogenic genes [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that Mef2a knockout mice displayed increased mortality in the first week of life, with severe, spontaneous RV chamber dilation [16]. miR-495 was able to induce the proliferation of neonatal cardiomyocytes in vitro [15]. It was also upregulated as prohypertrophic molecules in multiple models of cardiac diseases [17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Wang observed that miR-495 could regulate Bmi-1 to arrest the G1 to S phase transition in breast cancer [8]. Very recently, miR-495 was found to participate in Wnt signaling pathway regulation in cardiomyocyte proliferation [9], whose main function is to promote cell proliferation and differentiation [10,11]. However, little else is known about the reverse chain of miR-495, miR-495-3p, the implications of its function and expression in colon cancer.…”
Section: Introductionmentioning
confidence: 99%